Carisolv as an endodontic irrigant in deciduous teeth: An SEM study - Parul Singhal; Usha Mohan Das; Deepak Vishwanathan; Anita Singhal (Wolters Kluwer Medknow Publications, 2012)
Aim: Root canal irrigation plays an important role in the debridement and disinfection of the root canal system. "The purpose of this study was to evaluate the efficacy of Carisolv TM , 1% sodium hypochlorite (NaOCl) gel, and 1% NaOCl solution as root canal irrigants in deciduous anterior teeth." Materials and Methods: Thirty-six extracted deciduous anterior teeth were used. Root canals were flooded with NaOCl solution in Group A, NaOCl gel in Group B and Carisolv TM in Group C and incubated for 30 min. Scanning electron microscope photomicrographs of canal wall debris in the apical, middle and coronal thirds were scored. Results: The results showed that regardless of irrigation regime, canals were consistently cleaner in the coronal and middle thirds than in the apical thirds. NaOCl solution, NaOCl gel, and Carisolv TM had comparable activity at coronal third and middle third of root canals. At the apical third, NaOCl solution cleaned canals better than NaOCl gel and Carisolv TM . Carisolv TM cleaned debris better than NaOCl gel at the apical third. Conclusion: Carisolv TM can be used as an adjunct to root canal preparation.